2021
DOI: 10.1139/cjpp-2020-0202
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroxystilbene glucoside alleviates angiotensin II induced HUVEC senescence via SIRT1

Abstract: Tetrahydroxystilbene glucoside (TSG), an active ingredient of <i>Polygonum multiflorum</i>, has been known for certain anti-aging effects. In this study, the possible protective mechanism of TSG on human umbilical vein endothelial cells (HUVECs) senescence induced by angiotensin Ⅱ (Ang Ⅱ) was investigated. The results revealed that TSG pretreatment could reduce the percentage of senescence-associated-β-galactosidase (SA-β-gal) positive cells, and decrease the expression levels of the cellular senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Moldenke (Polygonaceae), is a popular traditional Chinese medicine that has been used for hair darkening, prolonging life, and mitigating several dysfunctions ( Tang et al, 2017 ). Modern pharmacological research and clinical practices have shown that RPM has several bioactive properties, including antioxidant ( Liu X. et al, 2021 ; Wang et al, 2008 ), antiaging ( Cheung et al, 2014 ; Fan et al, 2021 ), and antitumor activities ( Ma et al, 2012 ; Hou et al, 2013 ; Way et al, 2014 ; Lin et al, 2017 ; Xing et al, 2019 ), and it helps in regulating immunity ( Chen et al, 2012 ), lowering blood lipids ( Yao et al, 2013 ; Chang et al, 2016 ; Xie et al, 2012 ), and promoting neuroprotection ( Sun et al, 2011 ; Yang X.-P. et al, 2014 ; Ruan et al, 2021 ). However, an increasing number of recently published studies have demonstrated the adverse effects of RPM.…”
Section: Introductionmentioning
confidence: 99%
“…Moldenke (Polygonaceae), is a popular traditional Chinese medicine that has been used for hair darkening, prolonging life, and mitigating several dysfunctions ( Tang et al, 2017 ). Modern pharmacological research and clinical practices have shown that RPM has several bioactive properties, including antioxidant ( Liu X. et al, 2021 ; Wang et al, 2008 ), antiaging ( Cheung et al, 2014 ; Fan et al, 2021 ), and antitumor activities ( Ma et al, 2012 ; Hou et al, 2013 ; Way et al, 2014 ; Lin et al, 2017 ; Xing et al, 2019 ), and it helps in regulating immunity ( Chen et al, 2012 ), lowering blood lipids ( Yao et al, 2013 ; Chang et al, 2016 ; Xie et al, 2012 ), and promoting neuroprotection ( Sun et al, 2011 ; Yang X.-P. et al, 2014 ; Ruan et al, 2021 ). However, an increasing number of recently published studies have demonstrated the adverse effects of RPM.…”
Section: Introductionmentioning
confidence: 99%
“…The decreased SIRT1 expression and activity were closely associated with the progression of cellular senescence and cardiac dysfunction [ 115 ]. Conversely, SIRT1 activation confers protective effects on cellular senescence involving cardiovascular system [ 116 - 118 ]. Although the mechanisms remain unclear, SIRT1 inhibition-mediated p53 acetylation was implicated in aging-related cardiovascular disorders.…”
Section: Factors Regulating Senescence In Cardiovascular Diseasesmentioning
confidence: 99%
“…Further studies have shown that the mechanism of its anti-cutaneous aging effect is mainly through inhibiting the insulin/IGF-1 signaling pathway ( Zhou et al, 2014 ). In the angiotensin II-induced senescence model of HUVECs, TSG (20, 40 μg/ml) treatment decreased the percent of senescence-associated-β-galactosidase positive cells and the expression levels of cellular senescence biomarkers, p53 and PAI-1 protein ( Fan et al, 2021 ). Its anti-aging mechanism is mainly attributed to the regulation of SIRT1 activity ( Fan et al, 2021 ).…”
Section: Pharmacological Properties Of Tsgmentioning
confidence: 99%
“…In the angiotensin II-induced senescence model of HUVECs, TSG (20, 40 μg/ml) treatment decreased the percent of senescence-associated-β-galactosidase positive cells and the expression levels of cellular senescence biomarkers, p53 and PAI-1 protein ( Fan et al, 2021 ). Its anti-aging mechanism is mainly attributed to the regulation of SIRT1 activity ( Fan et al, 2021 ). Similarly, in the mouse model established by high calorie diet, TSG delayed the aging of aged mice consuming excess calories ( Ning et al, 2018 ).…”
Section: Pharmacological Properties Of Tsgmentioning
confidence: 99%
See 1 more Smart Citation